2018
DOI: 10.1007/s10266-017-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between skeletal morphology and agenesis of all four third molars in Japanese orthodontic patients

Abstract: The purpose of this study was to clarify differences in skeletal morphologies between male and female orthodontic patients with and without agenesis of all four third molars. A total of 64 patients (32 males and 32 females) with agenesis of all four third molars without agenesis of other teeth were selected as the third molars agenesis group (group 1). In addition, 64 patients (32 males and 32 females) with all these teeth were selected as controls (group 2). Lateral cephalograms taken between the ages of 14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The higher prevalence of M3 agenesis is similar to that of other studies which reported Class III malocclusions to have a higher prevalence of M3 agenesis than Class II malocclusions [5,21]. The high prevalence of these agenesis patterns in Class III malocclusions might be caused by the shorter maxillary length, as noted by Kajii [22] and Sugiki et al [23]. Kajii et al [22] demonstrated that with a decrease in the maxillary length, the prevalence of MxM3 and MnM3 agenesis was significantly increased.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The higher prevalence of M3 agenesis is similar to that of other studies which reported Class III malocclusions to have a higher prevalence of M3 agenesis than Class II malocclusions [5,21]. The high prevalence of these agenesis patterns in Class III malocclusions might be caused by the shorter maxillary length, as noted by Kajii [22] and Sugiki et al [23]. Kajii et al [22] demonstrated that with a decrease in the maxillary length, the prevalence of MxM3 and MnM3 agenesis was significantly increased.…”
Section: Discussionsupporting
confidence: 88%
“…Kajii et al [22] demonstrated that with a decrease in the maxillary length, the prevalence of MxM3 and MnM3 agenesis was significantly increased. Sugiki et al [23] noted that the maxillary length was significantly shorter in subjects with agenesis of all four M3s than in those with all of these teeth. This consideration was supported by the results of the one-way analysis of variance and Turkey's test, which demonstrated that Class III malocclusions exhibited a significantly shorter maxillary length (Ptm-A distance) than Class I and Class II malocclusions [23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 1 , 2 Nevertheless, some studies demonstrate that patients affected by dental agenesis present changes limited not only to the alveolar bone but also to maxillary growth and development. 3 , 4 , 5 , 6 , 7 These changes are more severe as the number of absent teeth increase 4 , 6 and differ according to the bone affected (maxillary, mandible, or both), 4 , 5 and its location in the dental arch (anterior or posterior). 4 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…However, the question about the origin of this condition remains, not only in dentistry but also in evolutionary biology and biological anthropology. Also certain morphological changes have been associated with its congenital absence such as a decrease in size of the maxillary and mandibular bones (Kajii et al, 2004), a decrease in jaw length, lower facial height, decreased mandibular plane angle and decreased gonial angle (Sugiki et al, 2018). Fernández et al reported an association between third molar agenesis and cleft lip and palate (Fernandez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%